A origem do zero - Padrão, Darice Lascala (2008)
The objective of this research paper is to study the origins of ZERO and the different challenges that have emerged throughout history before ZERO was considered an integral part of mathematics. The references below all show ZERO in different contexts: Sentidos Atribuídos ao Zero por alunos da 6ª série, article by Salvador and Nacarato (2003), presented at ANPED 2003; Sentido do Zero, by Guimarães, masters dissertation PUCSP 2008; A História do Zero, by Pinedo and Sbardelotto (2004) published on electronic bulletin nº3 Junior of Mathematics Education Knowledge and Research Group CEFET Paraná southwest unity Pato Branco Campus. This study shows how significant studying the history of mathematics is for improving the understanding of the researched subject. The basis for this paper is a historical survey on earlier civilizations which introduced ZERO in their numerical system, furthermore analyzing the mathematical challenges they encountered before finally arriving at a definition for nothing . The Babylonian civilization developed a positional sexagecimal system where they assigned a symbol to indicate the absence of a value in a numerical sequence. The Mayan people invented a positional numerical system based on 20, with an irregularity in the value relative to the third order. The Mayans assigned a sign in the shape of a shell to symbolize the absence of a value (zero). The numerical system established by the Chinese was a hybrid system where a symbol called ling indicated the absence of a value (zero).The Hindu civilization developed a numerical positional system based on 10, and also used symbols to indicate the absence of a value (nothing). Later this symbol became a number, the zero as we know it today. Thus by studying the difficulties overcome by these civilizations, it was possible to describe the development of ZERO from its origins until it became an integral part of numerical system